Retrospective and current state of forest territories of the border areas of the Bryansk region exposed to radioactive contamination - T. A. Marchenko; A. I. Radin; A. N. Razdaivodin (Радиационная гигиена)
The aim of the study is to analyze the accumulated data on the study of forest territories of the border regions of the Bryansk region that have been exposed to radioactive contamination for their involvement in economic activity, as well as the possible transfer of radioactive materials in forest fires. The area of recorded and unaccounted forests was estimated according to the “Forest Plan of the Bryansk Region for the period 2019-2028” and the results of the analysis of remote sensing data of the earth, the assessment of radiation pollution – according to the radiation surveys of the forest fund and radioecological monitoring of forests, assessment of cesium-137 content – according to radiation monitoring. In the course of the work, the dynamics of the transition of forests from the range of a high level of radioactive contamination to lower ones from 1991 to 2018 slightly changes the total area of contaminated forests by regions was revealed. Top-level values of cesium-137 content in the main types of forest combustible materials, which a dangerous factor is contributing to a significant increase in the content of radiocesium in atmospheric air and the transfer of radionuclides beyond the limits of radioactive contamination zones in a forest fire. The most radiation-hazardous is the forest litter, which contains more than 70% of the total cesium-137 reserve in forest combustible materials, the values of which reach values of 224 kBq / kg in the Krasnogorsk district of the Bryansk region. The obtained forecast of cesium-137 content in the forest litter by the zones of radioactive contamination of forests in the most polluted areas of the Bryansk region for the period up to 2046 indicates the preservation of a high degree of radioactive contamination of forests in the Krasnogorsk and Novozybkovsky districts after more than 60 years after the Chernobyl accident power plants. Due to the high class of natural fire hazard of forests in the south-west of the Bryansk region and the high risk of fires in contaminated areas, it is necessary to assess the degree of danger in the prevention and suppression of radioactive forest fires, especially criterion of the absorbed dose for workers in order to avoid the deterministic effect.